(untitled) (Research, Society and Development, 2025)
Objective: To report the experience of medical students in identifying epidemiological and sociocultural barriers and implementing educational strategies for the management of metabolic diseases in the Family Health Strategy (ESF) Parque Verde, in Belém-PA. Methodology: This is a descriptive study, of the experience report type, carried out over four months within the context of the Teaching, Service, Community, and Management Interaction module. Activities involved situational diagnosis of hypertension and diabetes records, qualified listening regarding lifestyle habits, and the realization of a practical educational intervention ("Healthy Breakfast") to demystify food costs. Results: A scenario of high prevalence of metabolic risk factors was identified, corroborated by municipal data indicating Belém has dyslipidemia rates exceeding 21%. The experience revealed that low adherence to non-pharmacological treatment was associated with myths regarding the high cost of a healthy diet. The practical intervention resulted in greater community engagement and reduced resistance to nutritional follow-up. Conclusion: The teaching-service integration allowed students to understand that managing metabolic diseases in vulnerable areas requires going beyond pharmacological prescription, adopting health education strategies that are culturally adapted and economically viable.